Role of Sodium/Calcium Exchangers in Tumors - Chovancova, Barbora; Liskova, Veronika; Babula, Petr; Krizanova, Olga (Biomolecules, 2020)
The sodium/calcium exchanger (NCX) is a unique calcium transport system, generally transporting calcium ions out of the cell in exchange for sodium ions. Nevertheless, under special conditions this transporter can also work in a reverse mode, in which direction of the ion transport is inverted-calcium ions are transported inside the cell and sodium ions are transported out of the cell. To date, three isoforms of the NCX have been identified and characterized in humans. Majority of information about the NCX function comes from isoform 1 (NCX1). Although knowledge about NCX function has evolved rapidly in recent years, little is known about these transport systems in cancer cells. This review aims to summarize current knowledge about NCX functions in individual types of cancer cells.
Keywords: Neoplasm Invasiveness; iontový transport; calcium; vápník; cancer cells; Ion Transport; pumpa pro výměnu sodíku a vápníku; Calcium; Neoplasms; zvířata; Humans; Sodium-Calcium Exchanger; nádory; invazivní růst nádoru; sodík; Sodium; apoptosis; lidé; sodium-calcium exchanger; Animals